Vestibular Derangement and Motion Intolerance in VATER Association. (22nd May 2017) - Samuel, Orit; Shupak, Avi; Eran, Ayelet; Tal, Dror
Abstract : VATER association is a nonrandom occurrence of congenital malformations: vertebral defects, anal atresia, tracheoesophageal fistula, renal defects, and radial bone anomalies. We report the case of a 19-year-old man with a childhood diagnosis of VATER association, who presented to the motion sickness clinic with severe seasickness. We discuss the clinical and laboratory diagnosis of vestibular pathophysiology, which was confirmed by MRI of lateral semicircular canal and vestibule dysplasia. We suggest the possibility of vestibular involvement as part of the developmental field defect associated with VATER syndrome, which hitherto has rarely been reported.